Aesthetic Education of Preschool Children - Maxkambayeva Shaxrizoda Xusan qizi; Binoqulova Dilnora Sirojiddin qizi (Scientific Trends, 2022)
This article describes the aesthetic education of preschool children in the process of continuous education, children's attitude to social life, and the educational process.
Keywords: aesthetics, education, attention, upbringing, perception, consciousness, development, first step, sound, goal, opportunity.